Strong Convergence of Non-Implicit Iteration Process with Errors in Banach Spaces - Yan Hao; Xiaoshuang Wang; Aihua Tong (Abstract and Applied Analysis)
The purpose of this paper is to study the strong convergence of a non-implicit iteration process with errors for asymptotically I-nonexpansive mappings in the intermediate sense in the framework of Banach spaces. The results presented in this paper extend and improve the corresponding results recently announced.